From Spatial Domination to Virtual Space Solidarity Tactics: Perjuangan Bersama Untuk Mengatasi Ketidakadilan Terhadap Penghayat Agama Lokal Minahasa - Pinatik, Hun Johanis Alfrits; Izak Y. M. Lattu; Tony Tampake (Jurnal Studi Agama, 2024)
Many studies have explored indigenous religious believers struggle against world religions domination. However, studies on the employment of virtual space to heighten indigenous believers' tactical solidarity from the Global South remain understudy. This paper explores indigenous religious followers' struggles through access to virtual space as a tactic of everyday solidarity against world religions spatial domination and the state politics of religion in North Sulawesi, Indonesia. It focuses on the efforts of Minahasa indigenous religious believers to advocate for their existence through virtual media collectively. Indigenous religious believers have experienced various forms of spatial domination, such as destroying ancestral sites and ritual places that they consider sacred to realize their beliefs. The single truth perspective has produced the domination of the world religions monotheistic paradigm and the state politics of religion. The single truth has resulted in hate speech, stigmatization, and physical destruction of indigenous religious sacred sites. Through click activism, indigenous religious believers employ virtual media to advocate Minahasa indigenous religions/beliefs. The concept of tactical media is used in this study to analyze how the tactics of indigenous religious believers collectively produce a discourse of resistance critique and discourse on the importance of their places of belief to the public. This study uses qualitative research: observation, in-depth interviews, and literature review to argue that indigenous religious believers have tactically used virtual media as a critical discourse of resistance to the spatial domination constructed by world religious relations and state religious policies.